Perception of the Arctic as Tourism Destination and Perspectives of its Utilization by Tourism Industry in Finnish Lapland - Malinin, Mikhail (Lapin ammattikorkeakoulu, 2014)
The aim of this thesis project was to analyse how the notion and brand image of the Arctic is perceived and understood, and how it could be exploited by tourism industry stakeholders in case of Finnish Lapland. The main focus was put on determining what associations people have about the Arctic, what images and attributes are most popular and how the Arctic is perceived as a tourism destination. The study also evaluated what tourism products and services are most expected and how high the level of preparedness to travel to the Arctic is. In order to find answers to the research question a quantitative survey was conducted with the help of structured questionnaires. The questionnaire was given to foreign visitors in Rovaniemi, Finland and to other people who do not live in the Arctic. The questions in the questionnaire inquired about the different aspects of perception of the Arctic as tourism destination: images associated with it, level of awareness of the existing tourism network, most expected tourism services, general level of preparedness to travel and possible factors which could hinder the travel. A qualitative interview was conducted with Ilona Mettiäinen, a researcher, who works at the Arctic Research center in Rovaniemi, and whose expertise is related to this topic. The findings indicate that this image is dominated by classic images of the high Arctic: icebergs, snow and ice. At the same time, there is a growing awareness about the local peoples, interest in their culture, handicrafts and food. However, the image of the Arctic is not very diversified. Most expected tourism products and services are mainly nature-related, but also those related to handicrafts, local cuisine, saunas and spa services are prominent, which implies that the possible service range which can impact the general image of the Arctic is quite wide. The most popular reason, seen as capable to hinder the travel is the high transportation costs, which can also serve as a future benefit for non-high Arctic areas.